MOLECULAR STUDIES OF SEVEN SPECIES OF BUTTERFLIES (LEPIDOPTERA: PIERIDAE) THROUGH RAPD-PCR TECHNIQUE - M.S.THAKUR (International Journal of Pharma and Bio Sciences, 2013)
In present investigations molecular characterization of seven Pieridae butterflies was carried out using four RAPD markers. A total 57 bands were scored with four decamer primers of which 57 were polymorphic and the percentage of polymorphism was 100%. Genus specific bands have been observed i.e. a band of 818bp with primer 12 & 520bp with primer OPP-5. Dendrogram constructed using the NTSYSspc2.2software divided the pierids into two clades. Cluster-I comprises of two species viz. Pieris brassicae nepalensis and Pieris canidia indica. Cluster-II comprises of 5 species viz. Colias electo fieldi, Colias erate erate, Gonepteryx rahmni nepalensis, Pontia daplidice moorei & Terias hecabe fimbriata. Cluster –II is subdivided into two, sub-cluster-I consisting of Colias electo fieldi, Colias erate erate, Terias hecabe fimbriata & Gonepteryx rahmni nepalensis, sub-cluster-II consists of only Pontia daplidice moorei.